Endophytic Colonization of Onions Induces Resistance Against Viruliferous Thrips and Virus Replication - Muvea, Alexander Mutua; Subramanian, Sevgan; Maniania, Nguya Kalemba; Poehling, Hans-Michael; Ekesi, Sunday; Meyhöfer, Rainer (Frontiers in Plant Science, 2018)
In agricultural ecosystems, insect pests, pathogens, weather patterns, and reduced soil fertility pose major challenges to crop productivity and are responsible for significant yield losses worldwide. Iris yellow spot virus (IYSV) vectored by Thrips tabaci Lindeman, is a major hindrance to onion production in eastern Africa. Control measures often rely on insecticides with deleterious effects. Endophytes are one key alternative as they can play important role in mediating induced systemic resistance. Hence, we examined the potential effect of endophytic fungus Hypocrea lixii (F3ST1) on feeding and replication of IYSV on endophyte-colonized (E+) and endophyte-free (E-) onion plants. For more precise assessment, replication was also tested using leaf disc bioassays and individual thrips. The number of feeding punctures was significantly lower in E+ as compared to E- plants. Disease level was significantly lower in E+ as compared to E- plants for four weeks post-exposure to thrips. IYSV replication was reduced by 2.5-fold in endophytic treatment on both whole plant and leaf disc assays. Thrips tabaci showed 2 times higher feeding activities on endophyte-free onion leaf discs as compared to the endophyte-inoculated leaf discs. Our results suggest potential utility of the endophytes to reduce feeding damage and virus infection on onion plants. Further studies should be conducted to elucidate the secondary metabolites involved in such endophyte-thrips-virus mediated interaction and determine whether the interactions extends for this and other onion varieties and viruses in a field conditions.